2018
DOI: 10.1177/0098628318779277
|View full text |Cite
|
Sign up to set email alerts
|

Keys to a Successful Job Talk

Abstract: Interviews for faculty positions in psychology often include a teaching demonstration or research talk, but there is little empirical data about what makes these job talks successful. Psychology faculty ( N = 303) described the job talks required at 4-year institutions and the attributes of a successful job talk. For both teaching demonstrations and research talks, being accurate and knowledgeable was of highest importance, but being practiced, open, and engaging were also important. However, significant diffe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
1
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 11 publications
1
1
0
Order By: Relevance
“…Previous surveys of search committee chairs indicated that fit with a position is the most essential characteristic of successful job candidates (Landrum & Clump, 2004;Sheehan et al, 1998), and the current research documented significant differences in the acceptable research and teaching qualifications at various institutions. Furthermore, the results of this study are consistent with previous work suggesting that the faculty hiring process differs significantly at baccalaureate, master's, and doctoral institutions (Boysen et al, 2018(Boysen et al, , 2019. Although finding that faculty at baccalaureate institutions have high standards for teaching qualifications and that faculty at doctoral institutions high standards for research qualifications was unsurprising, a less predictable finding was that the standards of master's faculty are more like baccalaureate faculty than doctoral faculty.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Previous surveys of search committee chairs indicated that fit with a position is the most essential characteristic of successful job candidates (Landrum & Clump, 2004;Sheehan et al, 1998), and the current research documented significant differences in the acceptable research and teaching qualifications at various institutions. Furthermore, the results of this study are consistent with previous work suggesting that the faculty hiring process differs significantly at baccalaureate, master's, and doctoral institutions (Boysen et al, 2018(Boysen et al, , 2019. Although finding that faculty at baccalaureate institutions have high standards for teaching qualifications and that faculty at doctoral institutions high standards for research qualifications was unsurprising, a less predictable finding was that the standards of master's faculty are more like baccalaureate faculty than doctoral faculty.…”
Section: Discussionsupporting
confidence: 87%
“…Differences in faculty roles at baccalaureate, master's, and doctoral institutions significantly affect the hiring process (Benson & Buskist, 2005;Boysen et al, 2018Boysen et al, , 2019. In one study, faculty described the characteristics of job applications that would lead to an immediate rejection, the so-called kisses of death (Boysen et al, 2019).…”
mentioning
confidence: 99%